Designing a Communication Strategy for a Start- Up Company - Fistein, Benjamin (2015)
This thesis outlines the fundamental theory of setting up a marketing communication strategy in a B2B start-up environment. The objective is to design a communication strategy for a start-up company from scratch, providing a detailed outline of the steps required and considerations to be included, based on the literature from the theoretical part. This thesis serves as a practical guide for the creation of a successful communication strategy in a B2B start-up - a topic which has not been covered sufficiently by academic literature to date. In order to design the promotional strategy, existing literature has been used to set up the theoretical groundwork, industry benchmarking and primary research has been conducted, and secondary research has been performed. As a result, recommendations have been formed, which will be implemented in practice. The implications of this thesis' output will therefore be that the suggestions can be evaluated in retrospect.